(In)tangible Teamwork - Bettina Paul (Humanimalia)
Sniffer-dog-teams are a vital, and at the same time highly contested, part of aviation security practices. Rooted in science and technology studies, cultural animal studies and sociology, the article explores the way nonhuman species, in this case sniffer dogs, appear within and against the logic of security ensembles at airports, both currently and in the aspiration for a fully-automated future. Based on the insights of non-participant observations, as well as interviews on more-than-human sensing practices in security contexts predominantly in Germany, the article explores how humans conceptualize nonhuman modes of sensation. While human dog handlers have to cope with the ambivalent requirements of their role working for the state, in which their nonhuman partner is classified as a supporting tool, they are confronted with the scepticism of the wider world concerning their reliability and capacity in odour detection. The sniffer dog handlers must therefore deal with nonknowledge, particularly when it comes to the question of how to ensure what their nonhuman partners smell. In conceptualizing their human-animal interaction as a performative dance of agency, nonknowledge can be characterized as the enactment of a productive force through the embodiment of sensual knowledge. In exploring the nexus of human perception and nonhuman sensitivity, the article contributes to the question of how the epistemology of knowing shapes interspecies sense-making in security related contexts.